Orbital Involvement in Systemic Mastocytosis. (7th January 2014) - Meena, Manju; Benger, Ross; Karnaukhvoa, Irina; Waring, Dale; Li, Yi-Chiao
Abstract: A 61-year-old female presented with a 3-day history of painful and reddened right eye with painful ocular movements. She had been diagnosed as having systemic mastocytosis 4 years earlier. Ocular examination showed Best Corrected Visual acuity of 6/6 right eye and 6/6 left eye. There was marked conjunctival injection and chemosis. The posterior segment was normal. The left eye was normal. Exophthalmometry showed 2 mm of right proptosis relative to the left eye. Computed tomography (CT) scans showed an ill-defined intra-conal lesion and enlargement of the lacrimal gland in the right orbit. A diagnostic biopsy was performed; the histopathology findings were of orbital mastocytosis. We present what our literature search suggests is the first biopsy-proven case of orbital mastocytosis.